Stymulowanie rozwoju południowych Włoch jako przykład interwencji państwa w odniesieniu do regionów opóźnionych - Klamut, Mirosława; Gogolewska, Jadwiga (Wydział Prawa i Administracji UAM, 1994)
The paper focuses on the Italian state's regulatory influence on regional development. Particularly the regional policy between 1950 and 1989 is described in great detail. The set of instruments known as extraordinary intervention has never functioned properly, for various reasons: the incompatibility between actions of different governments or their purposes, the absence of co-ordination of locally formulated regional plans, a low degree of concreteness. Notwithstanding this partially critical assessment of the Italian experience, it is suggested that some of t h e specific solutions may be used in Poland, because Poland's regional policy should now address the problems of underdeveloped regions and be move active in the enhancing of structural regional development.
The stimulation of southern Italy's development as an instance of state intervention in retarded regions